pH-responsive chitosan–silica nanoparticles for salicylic acid delivery to alleviate continuous cropping stress in ginseng cultivation - Wang, Jiajun; Li, Ling; Liu, Sizhang; Feng, Baowei; Xu, Zhefeng; Wang, Huan; Zhang, Tao; Chen, Xue; Li, Qiong; Chen, Changbao (Frontiers in Microbiology, 2025)
Continuous ginseng cultivation leads to soil degradation, which adversely affects seed germination and seedling growth. To address this issue, we developed chitosan-modified mesoporous silica nanoparticles loaded with salicylic acid (SA), hereafter referred to as CS@MSN-SA, as an innovative soil amendment. With a diameter of approximately 200 nm, these hollow mesoporous nanocarriers mediated the pH-responsive controlled release of SA under neutral and acidic conditions. Ginseng seeds were sown under four soil conditions: (1) new soil, (2) continuous cropping soil, (3) new soil treated with CS@MSN-SA, and (4) continuous cropping soil treated with CS@MSN-SA. A comprehensive analysis was conducted on the rhizosphere soil, including microbial community structure and diversity, carbon source metabolic potential, nutrient content, and enzymatic activities. The results showed that CS@MSN-SA treatment significantly enhanced the growth parameters and antioxidant activity of ginseng compared to the untreated continuous cropping soil. CS@MSN-SA improved soil nutrient levels (N, P, K, available forms, and organic matter), increased pH, and boosted enzymatic activity. It also promoted beneficial shifts in microbial community structure and richness while increasing the microbial utilization of amines, carbohydrates, and carboxylic acids. Statistical analysis revealed a significant correlation between microbial community abundance and soil property parameters. Overall, CS@MSN-SA nanoparticles effectively mitigated the negative effects of continuous cropping by improving soil fertility and microbial balance, thereby promoting seed germination and healthy seedling development during ginseng cultivation.